2013
DOI: 10.1152/japplphysiol.01301.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary chemoreflex responses are potentiated by tumor necrosis factor-alpha in mice

Abstract: Inhalation of tumor necrosis factor-alpha (TNF-α), a proinflammatory cytokine, induces airway hyperresponsiveness, and the underlying mechanism is not fully understood. Hypersensitivity of vagal bronchopulmonary C-fiber afferents is known to contribute to the airway hyperresponsiveness during an airway inflammatory reaction. Because activation of these afferents can elicit pulmonary chemoreflexes, this study was designed to determine if a pretreatment with TNF-α induced airway inflammation and enhanced the pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…For example, pronounced increases in the plasma levels of tumor necrosis factor-␣ (TNF-␣), interleukin (IL)-1, IL-6, and IL-10 have been reported in the studies when hemorrhage of similar intensity and duration of hypotension as that in our study was induced (1). Some of these cytokines such as TNF-␣ and IL-1␤ are known to exert potent stimulatory and/or sensitizing effects on vagal pulmonary C-fiber afferents (16,22,31).…”
Section: Discussionsupporting
confidence: 66%
“…For example, pronounced increases in the plasma levels of tumor necrosis factor-␣ (TNF-␣), interleukin (IL)-1, IL-6, and IL-10 have been reported in the studies when hemorrhage of similar intensity and duration of hypotension as that in our study was induced (1). Some of these cytokines such as TNF-␣ and IL-1␤ are known to exert potent stimulatory and/or sensitizing effects on vagal pulmonary C-fiber afferents (16,22,31).…”
Section: Discussionsupporting
confidence: 66%
“…An increase in the tissue temperature can increase the metabolic rate and production of CO 2 and hydrogen ion locally in the airway and lung tissue, which may induce the nonspecific hypersensitivity of pulmonary C-fibers (13). Acute hyperthermia can also elevate the levels of several inflammatory mediators such as arachidonic acid metabolites [e.g., prostaglandin E 2 (PGE 2 )] (6) and pro-inflammatory cytokines [e.g., tumor necrosis factor-␣ (TNF-␣)] in the tissue and blood (5); and the sensitizing effects of PGE 2 and TNF-␣ on bronchopulmonary C-fibers are well documented (18,23,30). Furthermore, it has been shown that increasing temperature to ϳ42°C shifts the TRPV1 channel activation curve from a nonphysiological positive voltage range toward the negative potential in a physiologically relevant voltage range (44).…”
Section: Discussionmentioning
confidence: 99%
“…The animal preparation and experimental methods were described in details by Lin et al [27]. Briefly, after mice were anesthetized by isoflurane inhalation, a small (~0.5 cm) mid-line incision was made on the ventral neck skin to expose the trachea.…”
Section: Airway Inflammation Induced By Tnfαmentioning
confidence: 99%
“…Results showed that the total number of leukocyte cells was significantly higher in the WT mice 1 day after a treatment with TNFα than that in each of the other four groups of mice. No significant difference was found between these four other groups [27]. More strikingly, the percentages of eosinophils and neutrophils in the TNFα (1 day) group were >15 folds higher than that in naïve, Veh, TNFα (7 days), and TNF −/− +TNFα groups, and no significant difference was found in either eosinophils or neutrophils between these four other groups [27].…”
Section: Airway Inflammation Induced By Tnfαmentioning
confidence: 99%
See 1 more Smart Citation